67.7k views
5 votes
-(-6x - 5) = 4(5x + 3)

A) -2

B) -1/2

C) 1/2

D) 2

Please help and show work!!

User Percutio
by
5.1k points

1 Answer

1 vote

Answer:


\large\boxed{B)\ -(1)/(2)}

Explanation:


-(-6x-5)=4(5x+3)\qquad\text{use the distributive property}\\\\-(-6x)-(-5)=(4)(5x)+(4)(3)\\\\6x+5=20x+12\qquad\text{subtrac 5 from both sides}\\\\6x=20x+7\qquad\text{subtract 20x from both sides}\\\\-14x=7\qquad\text{divide both sides by (-14)}\\\\x=-(7)/(14)\\\\x=-(1)/(2)

User ArchNoob
by
5.8k points